2020
DOI: 10.5562/cca3688
|View full text |Cite
|
Sign up to set email alerts
|

Flow-injection Determination of Glutathione, Penicillamine and Tiopronin Based on the Reduction of Copper(II)-neocuproine Reagent

Abstract: A new flow-injection spectrophotometric method for the determination of glutathione (GSH), penicillamine (PEN) and tiopronin (mercaptopropionyl glycine, MPG) in pharmaceutical formulations is reported. The method is based on the reduction of Cu(II)-neocuproine reagent to Cu(I)-neocuproine by GSH, PEN or MPG in buffered medium (pH = 3) to form a stable coloured complex (λmax = 458 nm). Experimental conditions were optimized by univariate method, resulting with linear calibration curves in concentration range fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A sample of pure 20 µg.mL -1 D-PEN spiked with half, equal and double fold excess concentration of selected interferences and 1.3×10 -3 M NQS in presence of 0.2M of sodium phosphate buffer, three excipients were analyzed. The acceptable recovery values (95-105%) demonstrated that, there were no interferences during the determination of D-PEN using new CFIA system, the results summarized in Table (7).…”
Section: Study Of Interferencesmentioning
confidence: 80%
See 2 more Smart Citations
“…A sample of pure 20 µg.mL -1 D-PEN spiked with half, equal and double fold excess concentration of selected interferences and 1.3×10 -3 M NQS in presence of 0.2M of sodium phosphate buffer, three excipients were analyzed. The acceptable recovery values (95-105%) demonstrated that, there were no interferences during the determination of D-PEN using new CFIA system, the results summarized in Table (7).…”
Section: Study Of Interferencesmentioning
confidence: 80%
“…The optimum concentration of the reagent NQS was studied by injecting different concentrations (3.3×10 -4 -5.4×10 -3 ) M using a homemade injection valve loading in (L2). The results in Figure (7) indicated that the 1.3×10 -3 M gave the highest value of absorbance expressed as peak height in mV (n=3) with high repeatability.…”
Section: Effect Of Nqsmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, studies have found that L-penicillamine (L-Pen) is toxic and can cause neuritis and marrow damage [ 24 , 25 ]. Currently, the methods for detection and isolation of penicillamine involve flow injection [ 26 ], chromatography [ 27 , 28 , 29 ], spectrometry [ 30 , 31 , 32 ], colorimetric method [ 33 ], and electrochemical method [ 34 , 35 , 36 , 37 ]. However, the electrochemical sensor is miniaturized and easy to prepare, which effectively avoids the defects such as complex sample preparation, long detection time and expensive chiral selector.…”
Section: Introductionmentioning
confidence: 99%
“…In light of its important biological and clinical significance, there have been increasing interest in developing analytical methods for GSH determination ( Steghens et al, 2003 ). GSH-recycling assay ( Tietze, 1969 ; Chowdhury et al, 2013 ) with commercial assay kits, fluorescence ( Cai et al, 2015 ), electrochemistry ( Gao et al, 2016 ), surface-enhance Raman spectroscopy (SERS) ( Saha and Jana, 2013 ; Zhu et al, 2021 ), colorimetry ( Lee et al, 2018 ), flow injection analysis ( Zitka et al, 2007 ; Kukoc-Modun et al, 2020 ), and high-performance liquid chromatography–mass spectrometry (HPLC–MS) ( Moore et al, 2013 ) have been documented. Among these methods, HPLC–MS has been a method of choice for the determination of GSH due to its advantages of sensitivity and specificity ( Moral et al, 2012 ; Avula et al, 2013 ; Moore et al, 2013 ; Sun et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%